Fancy yarns : their manufacture and application - Gong, R. H. (Woodhead publishing in textiles ;, 2002)
Fancy yarns are those produced with some deliberate discontinuity, introduced either into the colour or form of the article, with the intention of producing an enhanced aesthetic impression. Most fancy yarns are produced by specialist spinners using machines modified or specially developed for the purpose; others are produced from 'fancy slivers' used as minor components of yarns made by spinners with normal equipment; still others are made exclusively by filament yarns, using adaptations of the air-jet texturing process. This is the first reference book to be devoted to the design and manufacture of these complex yarns.